FORMULASI DAN EVALUASI SABUN CAIR EKSTRAK ETANOL BAWANG DAYAK (Eleutherine Bulbosa (Mill.) Urb) TERHADAP BAKTERI Staphylococcus Epidermidis - M. Andi Chandra; Aristha Novyra Putri; Sischa Chamella Bachrin (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Ethanol extract of dayak onion bulbs has antibacterial activity that can inhibit staphylococcus epidermidis bacteria with an inhibition zone value of 16.9 mm (strong) so that it has the potential to be developed into antibacterial liquid soap preparations. The research method uses experimental by testing the physical evaluation of liquid soap preparations which include organoleptic test, homogeneity, pH test, viscosity test, cleaning power test, foam height test, free alkali test, and stability test (Cycling Test) and antibacterial testing using the disc diffusion method. The results of the physical evaluation characteristics of dayak onion ethanol extract liquid soap meet the predetermined requirements. The results of antibacterial activity of dayak onion ethanol extract liquid soap have variations in the value of the inhibition zone category, namely at a concentration of 1% the value of the inhibition zone is 5.41 mm (weak), a concentration of 5% the value of the inhibition zone is 7.01 mm (medium), a concentration of 10% the value of the inhibition zone is 7.53 mm (medium), a concentration of 15% the value of the inhibition zone is 8.15 mm (medium) so it can be concluded thatdayak onion ethanol extract liquidsoap has potential as an antibacterial against Staphylococcus epidermidis bacteria.